Why are Joint Replacement Registries Needed? Part 2. Overview of Several National Registries of Knee Arthroplasty - Zazirnyi, I.M. (TERRA ORTHOPAEDICA, 2023)
Summary. Joint replacement registries are well established and have an important impact on decision making and clinical practice. The objective of this article is to review orthopedic registries to examine aspects of patient demographics, implant use, and revision outcomes in relation to knee replacement surgery. Six best known national arthroplasty registries with more than 10 years of data were selected for a review. Despite the geographic diversity, the demographics of patients referred for surgery and subcategories of surgeries were remarkably similar. For a cemented total knee replacement, minimally stabilized devices have been preferred in most countries, and a revision-free result can be expected in more than 94% of cases after 10 years. Partial replacement (lateral lateral or medial unicompartmental) was used in 6% to 15% of primary cases and had higher revision rates than total replacement, but had lower postoperative mortality and fewer infectious complications. Patellofemoral replacements are used in 1% or less of cases and have a high revision rate.